Mechanical Aspects of Intervertebral Disc Injury and Implications on Biomechanics - Desmoulin, Geoffrey Thor; Pradhan, Vikram; Milner, Theodore Edgar (Spine (Philadelphia, Pa. 1976), 2020)
This article comprises a review of the literature. The purpose of this study was to elucidate the different types of structural failures exhibited in intervertebral discs (IVDs), summarize their potential causes with respect to mechanical loading conditions and the consequences on cell homeostasis and biomechanics. Many studies have been performed to gain insight into how discogenic back pain progresses in humans both in vitro and in vivo as well as in animal disc models. However, there is a major need to summarize the common factors which initiate the structural failures observed in IVDs and the typical biomechanical changes. This work could help in developing mechanisms aiming to restore the biochemical and biomechanical balance of IVDs. The different types of structural failures encountered in IVDs were reviewed from published literature. The types of mechanical loading causing these injuries and their physiological and biomechanical consequences were then summarized and linked to ongoing research in this area. The most prominent structural failures associated with IVDs are annulus tears, disc prolapse, endplate damage, disc narrowing, radial bulging, and osteophyte formation in the vertebrae. IVDs were found to be vulnerable to compression, flexion, axial rotation, and complex loading mechanisms through single impact, cyclical, and continuous loading. However, chronic loadings had a more damaging impact on the spine. Significant consequences include imbalance of metabolic enzymes and growth factors, alteration in stress profiles of IVDs and a decrease in mechanical stiffness resulting in impaired biomechanics of the spine. The mode of loading has an important impact on the severity and nature of failures seen in IVDs and the resulting consequences to biomechanics. However, further research is necessary to better understand to the mechanisms that link injury to degeneration and regeneration of IVD tissues. 3.